Search for heavy resonances in final states with four leptons and missing transverse momentum or jets in pp collisions at √s= 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Journal of high energy physics, 2024)
A search for a new heavy boson produced via gluon-fusion in the four-lepton channel with missing transverse momentum or jets is performed. The search uses proton-proton collision data equivalent to an integrated luminosity of 139 fb−1 at a centre-of-mass energy of 13 TeV collected by the ATLAS detector between 2015 and 2018 at the Large Hadron Collider. This study explores the decays of heavy bosons: R → SH and A → ZH, where R is a CP-even boson, A is a CP-odd boson, H is a CP-even boson, and S is considered to decay into invisible particles that are candidates for dark matter. In these processes, S → invisible and H → ZZ. The Z boson associated with the heavy scalar boson H decays into all decay channels of the Z boson. The mass range under consideration is 390-1300 (320-1300) GeV for the R (A) boson and 220-1000 GeV for the H boson. No significant deviation from the Standard Model backgrounds is observed. The results are interpreted as upper limits at a 95% confidence level on the cross-section times the branching ratio of the heavy resonances.
ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser und weitere 2855
Gesehen am 15.10.2025